Are physiotherapists expected to be competent in digital health practice? Meta-synthesis of international physiotherapy practice competency standards - Merolli, Mark; Ahmed, Osman; McCreesh, Karen; Remedios, Louisa; Butler-Henderson, Kerryn (Physiotherapy theory and practice, 2024)
Digital health technology is progressively transforming physiotherapy practice. Despite a maturing body of literature relating to physiotherapy digital health capability, research examining digital health physiotherapy competency standards is both lacking and lagging. Examine international professional practice competency standards for physiotherapists to identify themes common to digital health practice competency, published by international peak organizations governing physiotherapy practice. Systematic meta-synthesis of international peak organization physiotherapy practice competency standards. The study was undertaken over nine stages. Competency statements related to digital health were extracted, and further coded into resultant themes. Eleven documents were analyzed. Fifty-two statements explicitly referenced digital health competency. Identified themes were as follows: 1) digital health data governance; 2) digital health data translation; and 3) digital health technologies. Where digital health-related competency statements do exist, they are skewed toward health information management activities. Digital health practice is currently under-represented in competency standards for physiotherapists. Workforce advancement in light of the burgeoning impact of digital health will prompt further updates to professional competency standards set by our peak organizations. This will have a flow on effect, whereby education providers (e.g. universities and other professional development providers) should consider curriculum and training that prepares individuals for digitally enabled practice.